Elevated plasma vitamin B12 levels and cancer prognosis: A population-based cohort study. (February 2016) - Arendt, Johan Frederik Håkonsen; Farkas, Dóra Körmendiné; Pedersen, Lars; Nexo, Ebba; Sørensen, Henrik Toft
Highlights: Measuring plasma vitamin B12 levels is used to diagnose vitamin B12 deficiency. Elevated plasma vitamin B12 has been associated with an increased cancer risk. This large cohort study shows that cancer patients with high B12 have increased mortality. This association was independent of cancer stage, comorbidity, age and sex. Further prospective studies are needed to examine the clinical applicability of these results. Abstract: Background: Elevated plasma vitamin B12 levels (cobalamin, Cbl) are associated with increased short-term cancer risk among patients referred for this laboratory measurement. We aimed to assess prognosis in cancer patients with elevated plasma Cbl. Methods: We conducted a population-based cohort study using data from Danish medical registries during 1998–2014. The study included 25, 017 patients with a cancer diagnosis and Cbl levels of 200–600 pmol/L (reference/normal range), 601–800 pmol/L and >800 pmol/L measured up to one year prior to diagnosis, and a comparison cohort of 61, 988 cancer patients without a plasma Cbl measurement. Patients treated with Cbl were excluded. Survival probability was assessed using Kaplan–Meier curves. Mortality risk ratios (MRR) were computed using Cox proportional hazard regression, adjusted for age, sex, calendar year, cancer stage and comorbidity, scored using the Charlson comorbidity index. Results: Survival probabilities were lower among patients with elevated Cbl levels than among patients with normal levels and among members of the comparison cohort [(1-year survival, %) Cbl: 200–600 pmol/L: 69.3%; 601–800 pmol/L: 49.6%; >800 pmol/L: 35.8%; comparison cohort: 72.6%]. Thirty-day mortality was elevated for patients with Cbl levels of 601–800 pmol/L or >800 pmol/L, compared to patients with levels of 200–600 pmol/L [(MRR (95% confidence interval): 601–800 pmol/L vs. 200–600 pmol/L: 1.9 (1.6–2.2); >800 pmol/L vs. 200–600 pmol/L: 2.7 (2.4–3.1)]. This association remained robust for 31–90-day and 91–365-day mortality, showing similar dose-response patterns. Conclusion: Cancer patients with elevated Cbl levels had higher mortality than those with normal Cbl levels. These findings may have clinical significance for assessing the prognosis of cancer patients.